Intestinal parasitic infections and prevalence of anaemia among tribal school going children: a one year study - Kumar, Sarvepalli Vijaya; Ramalingam, krishnan (International Journal of Contemporary Pediatrics, 2019)
Background: Intestinal parasitic infections are one of the neglected tropical diseases listed by world health organization. Parasitic infections among school going tribal children cause significant anaemia and malnutrition. Our study mainly focused on estimating the prevalence of intestinal parasitic infections and focused on iron deficiency anaemia among the tribal school going children. Methods: A prospective study for one year was conducted at a tertiary care hospital and study group was tribal children from hostels and schools. Ethical committee approval was obtained and study included collection of socio demographic data, anthropometric data, stool examination for intestinal parasitic infections, Hb% estimation by “Hemocue globinometer Hb 301 System” a portable hemometer for Hb estimation. S. iron, S. transferrin and Total iron binding capacity were also estimated. Statistical analysis was performed by using SPSS version 20 and analyzed. P value <0.05 was considered significant. Results: This 428 study participants with 66.36% boys and 33.64% girls were enrolled. The prevalence of parasitic infections was 42.06%. Protozoal infections were 41.11% when compared to helminthic infections (26.67%) and mixed infections in 32.22%. Entamoeba histolytica was the predominant protozoal parasite identified (30%) and Ascaris lumbricoides among the helminthic infection (13.3%). Presence of anaemia in the present study population was 11.21% and among the study group with parasitic infections it was 66.67%. Conclusion: To conclude, regular deworming practices, awareness regarding hand washing practices, iron and folic acid supplementation irrespective of nutritional status and health education could significantly reduce the incidence of anaemia associated with intestinal parasitic infections.